Pengembangan Media Pembelajaran Teka-Teki Silang “Keberagaman Kebudayaan Indonesia” Muatan Pelajaran IPS bagi Peserta Didik Kelas IV Sekolah Dasar - Vera Yuli Erviana (Proceedings Series on Social Sciences & Humanities, 2022)
This research is motivated by the limited use of learning media that has not been varied, only using textbooks as teaching materials and posters of cultural map images. This study aims to determine the steps of media development and to determine the quality of product development in the form of a crossword puzzle learning media book "Indonesian Cultural Diversity" content of social studies lessons for fourth grade elementary school students. This study uses the Research and Development (R&D) type of research, with the research model using the ADDIE model. The research subjects are media experts, material experts and learning experts. Data collection techniques using observation, interviews and questionnaires. Data analysis used qualitative and quantitative analysis. The results of the assessment from the validation sheet by media experts obtained a score of 77.77 included in the good category, validation by material experts obtained a score of 85.41 included in the very good category, validation by learning experts obtained a score of 82.50 included in the very good category and the results of the assessment Overall from the experts obtained an average score of 81.89 which is included in the very good category. The results of the study indicate that the development of crossword puzzle learning media can be said to be of high quality to use.